What is the host range of Phytophthora agathidicida in New Zealand - Ryder, J.M.; Waipara, N.W.; Burns, B.R. (New Zealand Plant Protection, 2016)
Phytophthora agathidicida is a virulent oomycete plant pathogen which is currently known to only infect Agathis australis in New Zealand Phytophthora species rarely have a single plant host so other hosts for P agathidicida are likely but unknown Phytophthora species are also often cryptic and sometimes asymptomatic on their host plants making it a challenge to identify their true host range Once an exotic Phytophthora species is introduced to an area it becomes virtually impossible to eliminate A sound understanding of a Phytophthoras epidemiology is needed to prevent its spread onto uninfected hosts This study determined whether P agathidicida has a wider host range than currently recognised Plant community composition was compared between healthy and infected kauri forest to detect possible susceptible species and detached leaf assays were utilised as a further screen of possible hosts Results showed a significant difference in species abundances between sites infected with P agathidicida and sites without P agathidicida that was unrelated to other potential variables Leaf assays also indicated several other native plant species other than A australis as possible carriers or hosts including Knightia excelsa and Leucopogon fasciculatus Identifying the host range of P agathidicida is important for optimising the design of future control strategies for this pathogen